A biomechanical model for cell polarization and intercalation during Drosophila germband extension. (10th September 2015) - Lan, Haihan; Wang, Qiming; Fernandez-Gonzalez, Rodrigo; Feng, James J
Abstract: Germband extension during Drosophila development features the merging of cells along the dorsal–ventral (DV) axis and their separation along the anterior–posterior (AP) axis. This intercalation process involves planar cell polarity, anisotropic contractile forces along cell edges, and concerted cell deformation and movement. Although prior experiments have probed each of these factors separately, the connection among them remains unclear. This paper presents a chemo-mechanical model that integrates the three factors into a coherent framework. The model predicts the polarization of Rho-kinase, myosin and Bazooka downstream of an anisotropic Shroom distribution. In particular, myosin accumulates on cell edges along the DV axis, causing them to contract into a vertex. Subsequently, medial myosin in the cells anterior and posterior to the vertex helps to elongate it into a new edge parallel to the body axis. Thus, the tissue extends along the AP axis and narrows in the transverse direction through neighbor exchange. Model predictions of the polarity of the proteins and cell and tissue deformation are in good agreement with experimental observations.